Chronic tendinopathy: effectiveness of eccentric exercise - Woodley, B. L.; Newsham-West, R. J.; Baxter, G. D. (British Journal of Sports Medicine, 2007)
Objectives: To determine the effectiveness of eccentric exercise (EE) programmes in the treatment of common tendinopathies.